Bordetella bronchiseptica infections in patients with HIV/AIDS: A case report and review of the literature. Issue 51 (23rd December 2021) - Gujju, Veena R.; Akram, Bushra; Shibib, Dena R.; McGhee, Miranda A.; Drevets, Douglas A.
Abstract: Rationale: Bordetella bronchiseptica is a common cause of upper respiratory tract infections in domesticated dogs and cats and a rare zoonotic pathogen in immunocompromised humans. With increasing numbers of people acquiring pets and spending time with them in confined spaces due to COVID-19 lockdowns, it is important to be aware of adverse health consequences brought about by this interaction. We present a case of B bronchiseptica pneumonia in a patient with human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) and review key characteristics of an additional 30 cases of B bronchiseptica infections in 29 patients with HIV/AIDS that were identified by literature review. Patient concerns: A 61-year-old male with HIV/AIDS who was not on antiretroviral therapy and had advanced immunosuppression with a CD4+ T-lymphocyte count of 3 cells/μL sought medical attention for multiple somatic issues including subjective fevers, shortness of breath, and intermittent chest pain. Diagnosis: Computed tomography of the chest identified bilateral nodular opacities in the lower lobes with scattered areas of ground glass opacities. B bronchiseptica was identified in sputum culture by mass spectrometry followed by supplementary biochemical testing. Interventions: Empiric broad-spectrum antibiotics were initiated and changed to levofloxacin after susceptibility testing was completed. Outcomes: The patient was discharged after symptomatic improvement with levofloxacin. Lessons: Pneumonia with interstitial infiltrates in the setting of advanced CD4 lymphocyte depletion is the most common clinical syndrome caused by B bronchiseptica in patients with HIV/AIDS, and may be accompanied by sepsis. Advanced immune suppression, as well as chronic medical conditions, for example, alcoholism, diabetes, and renal failure that compromise host defenses are also commonly found in cases of B bronchiseptica infection in patients who do not have HIV infection. Reported animal contact among patients was not universal. Isolates were susceptible to aminoglycosides, carbapenems, fluoroquinolones, but typically resistant to most cephalosporins.